Recoding strategies of German learners of English as a foreign language - Treutlein, Anke; Schöler, Hermann; Landerl, Karin (Reading and writing, 2017)
This study investigated whether German learners of English as a foreign language (EFL) acquire additional recoding strategies that they do not need for recoding in the consistent German orthography. Based on the psycholinguistic grain size theory (Ziegler & Goswami, 2005) we expected students with little experience in EFL to use the same small-grain recoding strategy as in German, while more advanced students were expected to switch flexibly between small and large grain size recoding strategies when reading English nonwords. German students in Grades 5, 7, and 9, as well as university students were presented with an experimental nonword reading paradigm introduced by Goswami, Ziegler, Dalton, and Schneider (2003) which assesses the effects of language (nonwords derived from German vs. English), orthographic neighborhood, item length and presentation format (blocked vs. mixed) on reading latencies and accuracies. The data were analyzed using hierarchical linear models. The youngest age group did not use larger units to read English nonwords, but mostly applied simple grapheme-phoneme translation, as they would in their first language. University students were able to switch flexibly between large- and small size recoding strategies.